Addressing the Escalating Costs of Healthcare Expenditure in Malaysia - Rasiah, Rajah (International Journal of Human and Health Sciences (IJHHS), 2024)
Malaysia’s total per capita expenditure on health spending rose from RM393.00 in 1997 to RM1,974.00 in 2019 in constant 2019 prices and is expected to grow by 8.3 percent per annum between 2023 till 2028, with public expenditure growing by 8.5 percent and private expenditure by 8.1 percent per annum. While the increasing health care expenditures does raise concerns, especially when it is expected to exceed Singapore, Thailand, the Philippines, and Indonesia soon, this paper seeks to address how some important components of healthcare expenditures have evolved between 2000 and 2021. It also seeks to examine the cost impact of healthcare expenditure faced by the poor. The focus on the poor is essential as healthcare invokes welfare characteristics that require special treatment, as it is not a normal good that has to reach the entire population. Consequently, the paper focuses on addressing the provision of healthcare in Malaysia so as to ensure that the qualitative and quantitative features of it demonstrates effective allocative governance in the interest of strengthening social welfare in the country. International Journal of Human and Health Sciences Supplementary Issue 02: 2024 Page: S10